2009
DOI: 10.1177/230949900901700327
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intra-Osseous Liposarcoma of the Femur: A Case Report

Abstract: We report a rare case of an intra-osseous liposarcoma of the proximal femur. A 26-year-old man presented with a 6-month history of left groin pain radiating to the knee and an antalgic gait. Radiology showed a predominantly fatty lesion in the medial aspect of the femoral neck extending toward the lesser trochanter; most of the marrow in the femoral neck had been replaced without evidence of an extra-osseous mass; and the posterior cortex had been destroyed. Histological and immunohistochemical analyses of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Torigoe et al reported no effect of high dose ifosfamide; a change to cisplatin and doxorubicin resulted in liver toxicity and deterioration [ 32 ]. Macmull et al [ 28 ] found no effect with doxorubicin, and when chemotherapy was changed to ifosfamide and etoposide no relapse after 16 months follow up. In a further two cases treated with chemotherapy, there was no reported efficacy, both patients dying within 1.5 years of follow-up [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Torigoe et al reported no effect of high dose ifosfamide; a change to cisplatin and doxorubicin resulted in liver toxicity and deterioration [ 32 ]. Macmull et al [ 28 ] found no effect with doxorubicin, and when chemotherapy was changed to ifosfamide and etoposide no relapse after 16 months follow up. In a further two cases treated with chemotherapy, there was no reported efficacy, both patients dying within 1.5 years of follow-up [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their diagnosis is based on clinical and radiological elements and is confirmed by anatomopathology, to which we must add immunohistochemistry and molecular biology techniques, in particular the amplification of MDM2 and CDK4 [ 3 ]. The primary bone localization of liposarcomas remains rare; in fact, liposarcomas represent only less than 0.1% of primary bone cancers [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT and MR imaging reveals predominantly fat-containing lesions but demonstrate aggressive features, including cortical erosion/destruction and an extraosseous extension of a soft tissue mass. 79…”
Section: Vascular Bone Tumorsmentioning
confidence: 99%